Aerodynamic performance and analysis of a hovering micro-scale shrouded rotor in confined environment. (April 2019) - Han, Han; Xiang, Changle; Xu, Bin; Yu, Yong
The aerodynamic characteristics of open rotor hovering in confined environment are extensively studied, but few papers focus on shrouded rotor. In order to study aerodynamic performance and flowfield characteristics of micro-scale shrouded rotor hovering in confined environment, experimental measurements and computational fluid dynamic simulations are conducted in this article. Three cases of confined planes including ground, ceiling, and wall close to shrouded rotor are studied successively. Another case of no confined planes around shrouded rotor is also researched. Results show that both ground and ceiling improve the aerodynamic performance of shrouded rotor at distance below 1.5 rotor radii with the enhanced figure of merit, while wall plane influences flight stability because of the unbalanced moment. The experimental data reveal that the performance of shrouded rotor in-ground effect is more sensitive than that of shrouded rotor in-ceiling effect. However, for in-ground effect or in-ceiling effect, the performance of shrouded rotor is more sensitive than that of open rotor. Flowfield analysis by computational fluid dynamic shows the confined planes block airflow around shrouded rotor. Tip flow leakage and flow separation occur near shroud lip when shrouded rotor is hovering considerably close to ground or ceiling. Turbulent vortices and fluctuating velocities affect the flight stability of shrouded rotor.